Pengaruh Kondisi Operasi terhadap Karakteristik Pengeringan Jahe Merah (Zingiber officinale Var. Rubrum) Menggunakan Tray Dryer dengan Udara Panas dari Proses Pirolisis - Hasibuan, Rosdanelli; Hamdanah Hasibuan; Yovani Nissi Madani; Viqry Pramananda; Risma Fazillah; Vikram Alexander (Jurnal Teknik Kimia USU, 2023)
Red ginger (Zingiber officinale Var. Rubrum) is a rhizome plant often used as a complementary spice, a mixed ingredient in the food and beverages, and herbal medicines. One of the post-harvest processing of red ginger is drying, which aims to reduce the water content of red ginger to a point where the growth of microorganisms and the activity of enzymes that can damage red ginger can be prevented. This study aims to evaluate the effect of tray height and drying air temperature on moisture content, drying rate, drying characteristics, and quality of red ginger dried using a tray dryer with hot air from a biomass pyrolysis process. The results showed that both tray height and drying temperature affected red ginger's water content and drying rate. The quality of red ginger that complies with SNI 1-3393-1994 was obtained at a tray height of 60 cm and a drying temperature of 70 Â°C, with distinctive aroma and taste characteristics, the water content of 8,9%; ash content of 5,5%; oil content of 4,93 mL/100 g; and no fungus on the red ginger.